2006
DOI: 10.1111/j.1744-1617.2006.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence, Dove, and Divorce Mediation

Abstract: The primary objective of this article is to describe DOVE, a 19-item instrument designed to assess and manage the risk of domestic violence between partners during and following their participation in divorce mediation. Assessing risk, more specifically how DOVE can be used to assess risk, is described first. The resulting risk scores (TOTDOVE) are used to assign individuals to risk categories. Problems associated with using categorical, frequency, and probability risk assessment formats in interpreting and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…In general, most researchers fall somewhere between these two extreme positions (Beck & Frost, 2007;Ellis & Stuckless, 2006;Johnston & Campbell, 1993;Kelly & Johnson, 2008;Salem & Dunford-Jackson, 2008;Ver Steegh & Dalton, 2008). There is general agreement that at the very least there need to be adequate screening measures for IPA in couples attempting mediation (Beck & Sales, 2001;Ellis, 2008;Mathis & Tanner, 1998;Salem & Dunford-Jackson, 2008;Ver Steegh & Dalton, 2008).…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…In general, most researchers fall somewhere between these two extreme positions (Beck & Frost, 2007;Ellis & Stuckless, 2006;Johnston & Campbell, 1993;Kelly & Johnson, 2008;Salem & Dunford-Jackson, 2008;Ver Steegh & Dalton, 2008). There is general agreement that at the very least there need to be adequate screening measures for IPA in couples attempting mediation (Beck & Sales, 2001;Ellis, 2008;Mathis & Tanner, 1998;Salem & Dunford-Jackson, 2008;Ver Steegh & Dalton, 2008).…”
mentioning
confidence: 96%
“…An instrument created by Newmark et al (1995) was compiled from several existing measures including the Conflict Tactics Scale (Straus, 1979), the Procedural Justice Scale (Roehl, 1988), and the Marital Power and Decision-Making Scale (Blood & Wolfe, 1960). Several additional screening instruments have been created (Erickson & McKnight, 1990;Michigan Supreme Court, 2006;Neilson & Guravich, 1999), but to date, only one (Ellis & Stuckless, 2006) has been subjected to any empirical research and only with a limited sample.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These risk factors have emerged from research and domestic violence death review committees, which have identified characteristics most closely associated with lethal violence (see Campbell, 1995;Campbell, Sharps, & Glass, 2001;Ellis & Stuckless, 2006;Hilton et al, 2004;Kropp, Hart, Webster, & Eaves, 1994. Commonly reported factors include separation within the 176 P. G. Jaffe et al…”
Section: Assessing Domestic Violence Allegationsmentioning
confidence: 99%